PrPC Directly Interacts with Proteins Involved in Signaling Pathways - Christian Spielhaupter; Hermann Schätzl (2001)
The cellular prion protein (PrP(C)) is a conserved glycoprotein predominantly expressed in neuronal cells. Its purpose in living cells is still enigmatic. To elucidate on its cellular function, we performed a yeast two-hybrid screen for interactors. We used murine PrP(C) (amino acids 23-231) as bait to search a mouse brain cDNA expression library. Several interaction partners were identified. Three of them with a high homology to known sequences were further characterized. These candidates were the neuronal phosphoprotein synapsin Ib, the adaptor protein Grb2, and the still uncharacterized prion interactor Pint1. The in vivo interaction of the three proteins with PrP(C) was confirmed by co-immunoprecipitation assays with recombinant and authentic proteins in mammalian cells. The binding regions were mapped using truncated PrP constructs. As both synapsin Ib and Grb2 are implicated in neuronal signaling processes, our findings further strengthen the putative role of the prion protein in signal transduction.